2021
DOI: 10.1108/jbsed-01-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive financial innovations: the case of Nigerian micro-entrepreneurs

Abstract: PurposeDespite the noticeable consequences of disruptive financial innovations, access to finance remains a major factor inhibiting the sustainable-growth potentials of young micro-entrepreneurs in informal settings. This study examines the determinants of financing options among micro-entrepreneurs in informal settings. Specifically, the study seeks to establish whether credit history, income, asset, gender, awareness and network capability have effects on formal and informal financing options among micro-ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In the last 2 decades, a drastic transition of economies has emerged, from a traditional-driven approach to a more knowledge-intensive driven approach (Ali and Anwar, 2021; Vidyarthi, 2018). The change is in line with the catch-up of economies with Industrial Revolution 4.0 with particular insights into competitiveness and value creation (Adeosun et al. , 2021; Ofori-Sasu et al.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the last 2 decades, a drastic transition of economies has emerged, from a traditional-driven approach to a more knowledge-intensive driven approach (Ali and Anwar, 2021; Vidyarthi, 2018). The change is in line with the catch-up of economies with Industrial Revolution 4.0 with particular insights into competitiveness and value creation (Adeosun et al. , 2021; Ofori-Sasu et al.…”
Section: Introductionmentioning
confidence: 79%
“…In the last 2 decades, a drastic transition of economies has emerged, from a traditional-driven approach to a more knowledge-intensive driven approach (Ali and Anwar, 2021;Vidyarthi, 2018). The change is in line with the catch-up of economies with Industrial Revolution 4.0 with particular insights into competitiveness and value creation (Adeosun et al, 2021;Ofori-Sasu et al, 2019). Thereafter, knowledge became a vital tool for achieving a sustained competitive advantage for the economies and firms domiciled in such economies (Nitkiewicz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have empirically confirmed the significant effects of HC, SC, OC and financial capital on business performance in emerging markets (Al Mamun et al, 2018;Huang, 2016;Jordão et al, 2022;Jordão and de Almeida, 2017) and developed economies (Ju et al, 2019;Liu et al, 2020;Sardo et al, 2018). For instance, HC enhances performance by solving firms' problems (Jordão et al, 2022;Khan et al, 2021a;Liu et al, 2020;Sallah and Caesar, 2020), SC by building positive relationships (Jordão et al, 2020;Jordão and de Almeida, 2017;Li et al, 2021;Sardo et al, 2018), OC by raising the process value and promoting growth (Chege et al, 2020;Jordão et al, 2020;Jordão and de Almeida, 2017;Lau and Rowley, 2021;Sardo et al, 2018) and AFC by facilitating success and overall performance (Adeosun et al, 2021;Ju et al, 2019;Kee et al, 2019;Khan et al, 2021a). In addition, TR and PR significantly affect business performance.…”
Section: Entrepreneurial Resources and Micro Business Performancementioning
confidence: 84%
“…Scholars have defined these resources based on their significance. For instance, AFC from formal financial institutions and informal sources (friends, family and money lenders) have been determined to be a significant factor in achieving business success and improving overall performance (Adeosun et al , 2021; Kee et al , 2019; Khan et al , 2021a). HC is described as the accumulation of abilities, knowledge and skill sets to increase competitiveness (Jordão et al , 2020; Samad, 2020).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Over the past decades, technology has evolved at a fast rate and been globally adopted and integrated into all aspects of life, and because of the efficiency and problem-solving capacity E-payment acceptance 107 it provides, we have become dependent on it. Financial services are one of the major beneficiaries of technology (Adeosun et al, 2021) leading to the development of financial technology (FinTech).…”
Section: Introductionmentioning
confidence: 99%